O professor da escola pública do Rio de Janeiro: de que conformismos e conformista? - Correa, Vera Maria de Almeida (2012)
Submitted by Estagiário SPT BMHS (spt@fgv.br) on 2012-02-03T13:05:13Z No. of bitstreams: 1 000056767.pdf: 15069657 bytes, checksum: d620bc742a547034c35ba0acb582b975 (MD5) === Made available in DSpace on 2012-02-03T13:05:22Z (GMT). No. of bitstreams: 1 000056767.pdf: 15069657 bytes, checksum: d620bc742a547034c35ba0acb582b975 (MD5) Previous issue date: 1991 === The present work deals with the process at political formation of public school teacher in Rio de Janeiro through his/her union practice, from 1979 on. It represents an attempt to understand the teacher’s process of emergence as a citizen who looks for organization in civil society, counteracting the work on this teacher’s formation the dominant ideology has tried to solidify throughout history. Starting from the Gramscian categories, we tried to understand the teacher’s process of building a critical consciousness. Next, we tried to establish the relation between the economical-political-social situation of the last decades and the shaping of the teacher’s category as a worker, through a retrospective of the Brazilian socio-historical process, from 1930 on. Later, after the critical review of the history of the State Teacher’s Center of Rio de Janeiro (Centro Estadual dos Professores do Rio de Janeiro – CEP/RJ), we analyzed the political formation process of the interviewed leadership emphasizing their assessment of the routes of this union movement and its representation on the 'conformities' the public school teachers of Rio de Janeiro conform with. The conclusion points at some of the determinations which interact in the process of overcoming the naïve consciousness and emerging of a critical consciousness, in the perspective of class consciousness, emphasizing the importance of social relations viewed as pedagogical ones. === O presente trabalho trata do processo de formação política do professor da escola pública do Rio de Janeiro na sua prática político-sindical, a partir de 1979. Representa uma tentativa de apreender o processo de emergência do professor, enquanto cidadão que se organiza na sociedade civil em contraposição ao trabalho de conformação que a ideologia dominante busca, historicamente, solidificar. Partindo-se de categorias gramscianas, busca-se o entendimento do processo de constituição da consciência crítica. A seguir, numa retrospectiva do processo de construção histórico-social brasileiro desde 1930, procura-se estabelecer a relação entre a conjuntura econômica, política e social das últimas décadas e a constituição da categoria do professor, enquanto trabalhador assalariado. Posteriormente, após a reconstrução crítica da história do Centro Estadual dos Professores do Rio de Janeiro – CEP/RJ, analisa-se o processo de formação política das lideranças, destacando-se a avaliação que elas fazem sobre os rumos desse movimento sindical, bem como as suas representações sobre os 'conformismos' de que são conformistas os professores da escola pública do Rio de Janeiro. Conclui-se apontando para algumas das sobredeterminações que interagem no processo de superação da consciência ingênua e a emergência da consciência crítica, no horizonte da consciência de classe, destacando-se a importância das relações sociais enquanto relações pedagógicas.